Dry Port Development: A Systematic Review - Fatimazahra BENTALEB (Journal of ETA Maritime Science, 2015)
Studies on dry ports as nodes in multimodal transport have been expanded to decrease the mounting congestion on seaports. The principal objective of this study is to inspect how dry port researches have been conducted from different perspective. This paper tries to recap the existing researches that aimed to study dry port concept via a systematic review, to present a general overview of the researches on our relevant region and propose a classification for these researches. This paper present a systematic review of dry port that looks to illustrate the progress of researches on this area between 1986 and 2015, collecting researches on dry port concept and analyzing the main characteristics of the dry port development and their contribution to the multimodal transport. The results indicated that most dry port studies considerate the strategic level and concentrate in the Asian continent. Studies regarding other decision levels and continents have to be developed in further researches. Although the existing studies make a contribution in dry port concept, they allow gaps in terms of operational and tactical decision levels considering their limited geographical region.